2015
DOI: 10.19173/irrodl.v16i3.2202
|View full text |Cite
|
Sign up to set email alerts
|

Who studies MOOCs? Interdisciplinarity in MOOC research and its changes over time

Abstract: The complexity of digital and online education is becoming increasingly evident in the context of research into networked learning/participation. Interdisciplinary research is often proposed as a way to address complex scientific problems and enable researchers to bring novel perspectives into a field other than their own. The degree to which research on Massive Open Online Courses suggest that empirical research on xMOOCs may be more interdisciplinary than research on cMOOCs. Greater interdisciplinarity in xM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 23 publications
2
36
0
4
Order By: Relevance
“…Later on, the review of 60 papers published from 2008 to 2014 identified nine research categories based on research aims of each article, and concluded that the field of MOOC studies heavily relied on theoretical research and was just beginning to identify appropriate research methods to deal with large cohorts of participants, huge amounts of data, and innovative approaches of learning [14]. More recently, the review of 183 articles published during the period 2013-2015 revealed that MOOC studies had become more interdisciplinary than research pieces published from 2008 to 2012 [15].…”
Section: Previous Reviews On Mooc Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Later on, the review of 60 papers published from 2008 to 2014 identified nine research categories based on research aims of each article, and concluded that the field of MOOC studies heavily relied on theoretical research and was just beginning to identify appropriate research methods to deal with large cohorts of participants, huge amounts of data, and innovative approaches of learning [14]. More recently, the review of 183 articles published during the period 2013-2015 revealed that MOOC studies had become more interdisciplinary than research pieces published from 2008 to 2012 [15].…”
Section: Previous Reviews On Mooc Literaturementioning
confidence: 99%
“…The existing review articles seem to suggest that research topics on MOOCs are diverse [12], [14], and the research trend is continually evolving [13]- [15]. Among many topics investigated by MOOC scholars, teaching and learning has received increasing scholarly attention [14], [16].…”
Section: Previous Reviews On Mooc Literaturementioning
confidence: 99%
“…While the MOOC phenomenon has been subject to numerous interpretations in the mass media (Kovanović, Joksimović, Gašević, Siemens, & Hatala, 2015;Selwyn, Bulfin, & Pangrazio, 2015) and some analyses of the the state of the field have been published (e.g., Bayne & Ross, 2014;Ebben & Murphy, 2014), researchers currently lack a systematic synthesis of the empirical literature published on the topic. A collective research effort is required to fully understand the impact of MOOCs (Reich, 2015), and researchers will benefit from analyses and syntheses of the literature, especially because (a) the field has developed rapidly and sparked extensive conversations pertaining to education and educational technology, (b) meaningful research results appear to be sparse (Jona & Naidu, 2014), and (c) researchers studying MOOCs reside in diverse disciplines (Veletsianos & Shepherdson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The 21 st century witnessed an educational paradigm shift, stemming from the widespread use of (Weller, 2014): It is suggested There have been some efforts in academia to understand and analyse the MOOC phenomenon; several papers have examined MOOC research in academic journals (Ebben & Murphy, 2014;Gasevic, Kovanovic, Joksimovic, & Siemens, 2014;Kennedy, 2014;Liyanagunawardena et al, 2013;Raffaghelli, Cucchiara, & Persico, 2015;Sa'don, Alias, & Ohshima, 2014;Sangrà, González-Sanmamed, & Anderson, 2015;Veletsianos & Shepherdson, 2015Bozkurt, Akgün-Özbek, & Zawacki-Richter, 2017). These papers examined aspects of MOOC research such as methodology, pedagogy, and theory.…”
Section: Introductionmentioning
confidence: 99%